# Find the sum of the first n

821 views (last 30 days)

Show older comments

##### 0 Comments

### Answers (3)

John Chilleri
on 15 Feb 2017

Edited: John Chilleri
on 15 Feb 2017

Hello,

This can be done simply with,

n = 100; % whatever you want

sum_harm = 0;

for i = 1:n

sum_harm = sum_harm + 1/i;

end

or even,

n = 100; % whatever you want

sum_harm = sum(1./(1:n));

Hope this helps!

##### 7 Comments

Walter Roberson
on 4 Jun 2021

format long g

n = 1e10; % whatever you want

sum_harm_forward = 0;

sum_harm_reverse = 0;

for i = 1:n

sum_harm_forward = sum_harm_forward + 1/i;

sum_harm_reverse = sum_harm_reverse + 1/(n - i + 1);

end

sum_harm_forward

sum_harm_reverse

sum_harm_forward - sum_harm_reverse

Roger Stafford
on 15 Feb 2017

Or how about this one-liner:

H = det(diag(2:n)+ones(n-1))/factorial(n);

##### 2 Comments

Walter Roberson
on 8 Sep 2018

syms x n

symsum(1/x, x, 1, n)

##### 1 Comment

Hesbon Osoro
on 3 Jun 2021

### See Also

### Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!